DIAGNOSTIC ACCURACY OF RISK OF MALLIGNANCY INDEX (RMI) BASED ON SERUM CA 125, ULTRASOUND SCORE AND MENOPAUSAL STATUS IN DETERMINING THE MALIGNANCY RISK IN ADNEXAL MASS - Rabia Syed; Neelam Hassan; Sundas Khurshid; Nazma Gul; Sara Akram; Attia Aziz Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: The presence of an adnexal mass is a frequent reason for a woman to be referred to a gynecologist. An adnexal mass may be benign or malignant. It is the risk of malignancy that propels us for early, accurate and prompt diagnosis to lessen mortality and morbidity. Objective: To determine diagnostic accuracy of risk of mallignancy index (RMI) based on serum ca 125, ultrasound score and menopausal status in determining the malignancy risk in adnexal mass Methodology: This cross-sectional study was conducted in the Department of Obstetrics & Gynecology, Allama Iqbal Teaching Hospital, Dera Ghazi Khan, from May 10th, 2023, to November 10th, 2023. The sample size of 100 women was determined using WHO software for sample size calculation. Patients between the ages 25-75 years, presenting with any symptom and diagnosed to have adnexal mass diagnosed on ultrasound were enrolled. Detailed history of patient, clinical examination, preoperative serum CA 125 levels and Trans-abdominal abdominopelvic ultrasound was performed. Characteristics of mass were determined on ultrasonography by a senior radiologist. Data was analyzed on SPSS version 23. Results: The average age of study patients was 29.4 + 5.5 years. Primary infertility was experienced by 30.0% women whereas secondary infertility was found in 45.0% women in this study. It was witnessed that 96.0% of the study women had disturbed menstrual cycles and 19.0% had passage of clot. The pre-operative mean CA 125 level was 60.5 + 46.4 IU/ml while post operatively after 6 weeks it was found at 27.5 + 17.5 IU/ml and this difference between pre operative and post operative CA 125 levels was highly statistically significant (p-value = <0.001). The percentage decrease was 45.1% from preoperative readings to post operative levels of CA 125 in this study. Conclusion: The risk of malignancy index to be a valuable, reliable, and applicable method in the primary evaluation of patients with ovarian masses and a usable method in referral of relevant patients for centralized surgical treatment.